Modeling for Partially Spatially Coherent Vortex Beams - Zhangrong Mei (IEEE Photonics Journal)
We propose a method for modeling a wide class of partially spatially coherent vortex beams. It is shown that any member of such beams can be represented as an incoherent superposition of fully coherent vortex models weighted by a non-negative weighting function. Applying this method, we introduce a new type of partially coherent vortex beams and study its far-field properties.